2017
DOI: 10.1016/j.psychres.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

ADHD and nonsuicidal self-injury in male veterans with and without PTSD

Abstract: The objective of the present research was to examine the association between ADHD symptoms and nonsuicidal self-injury (NSSI) in male Iraq/Afghanistan-era veterans with and without PTSD. Approximately 25% of veterans screened positive for clinically-significant levels of ADHD. Male veterans with PTSD were significantly more likely to report ADHD symptoms than male veterans without PTSD. In addition, as expected, ADHD was strongly associated with NSSI, even after accounting for the effects of demographic variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
4
7
0
Order By: Relevance
“…0%;Bloshnich et al, 2015;Bryan & Bryan, 2014;. Prevalence observed in this study fits within the range found in prior studies that have utilized NSSI assessment tools explicitly evaluating SDV intent among clinical and community samples of veterans (6%-25%; Chu et al, 2018;Holliday et al, 2018;Kimbrel et al, 2015Kimbrel et al, , 2016Kimbrel et al, , 2017Kimbrel, Meyer, et al, 2018). By contrast, it is notably lower than rates observed in studies that have examined NSSI using the Habit Questionnaire (Resnick & Weaver, 1994), which…”
Section: Aim 1: Describe Clinical and Behavioral Characteristics Ofsupporting
confidence: 80%
See 3 more Smart Citations
“…0%;Bloshnich et al, 2015;Bryan & Bryan, 2014;. Prevalence observed in this study fits within the range found in prior studies that have utilized NSSI assessment tools explicitly evaluating SDV intent among clinical and community samples of veterans (6%-25%; Chu et al, 2018;Holliday et al, 2018;Kimbrel et al, 2015Kimbrel et al, , 2016Kimbrel et al, , 2017Kimbrel, Meyer, et al, 2018). By contrast, it is notably lower than rates observed in studies that have examined NSSI using the Habit Questionnaire (Resnick & Weaver, 1994), which…”
Section: Aim 1: Describe Clinical and Behavioral Characteristics Ofsupporting
confidence: 80%
“…As one example, research on treatment‐seeking attitudes among active duty service members suggests distinct barriers to disclosing mental health concerns that do not exist for veterans, such as future‐oriented concerns about one's military career (Hom, Stanley, Schneider, & Joiner, 2017). Relatedly, nine of the fourteen studies assessed NSSI in specialized veteran populations, including veterans specifically enrolled in college courses (Blosnich et al, 2015; Bryan & Bryan, 2014; Bryan et al, 2015) or veterans oversampled for PTSD diagnosis (Calhoun et al, 2017; Cunningham et al, 2019; Kimbrel et al, 2015, 2016, 2017) or history of military sexual trauma (MST; Holliday et al, 2018), potentially limiting generalizability to veterans outside these unique diagnostic or environmental circumstances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-suicidal self-injury (NSSI), defined as the deliberate, self-inflicted damage of any body tissue without suicidal intent and for purposes not socially or culturally sanctioned (International Society for the Study of Self-Injury, 2018), is a strong prospective predictor of suicide attempts (SA) in civilian populations (Asarnow et al ., 2011; Wilkinson et al ., 2011; Hamza et al ., 2012; Ribeiro et al ., 2016). Yet, to our knowledge, only a handful of published studies have investigated the prevalence and characteristics of NSSI in military samples (Klonsky et al ., 2003; Bryan and Bryan, 2014; Kimbrel et al ., 2014; Shelef et al ., 2014; Bryan et al ., 2015 a , 2015 b ; Kimbrel et al ., 2015, 2016, 2017; Calhoun et al ., 2017; Baer et al ., 2018). Like civilian samples, NSSI in military samples is more prevalent in women (Bryan and Bryan, 2014; cf.…”
mentioning
confidence: 99%